Impingement-Free Hip Flexion in Asymptomatic Young Adult Women. (4th November 2020) - Mahan, M. Chad; Yu, Charles C.; Shields, Rachel; van Holsbeeck, Marnix; Zaltz, Ira
Abstract : Background: Ultrasound-assisted measurement of hip flexion has demonstrated that hip flexion has been historically overestimated in men. To our knowledge, assessment of hip flexion in women using similar methods has not been reported. Establishing normative values for hip flexion is vital to aid diagnosis, management, and future research. Therefore, we asked 2 questions: (1) At what range of midsagittal hip flexion do soft-tissue impingement and femoroacetabular abutment occur in asymptomatic young adult women? (2) Do radiographic findings on a supine anteroposterior pelvic radiograph correlate with ultrasound-assisted measurements of hip flexion? Methods: Fifty-five asymptomatic adult women volunteers (107 hips) underwent ultrasound-assisted assessment of hip flexion. Hip flexion was recorded at the initiation of labral contact and at bone-on-bone contact. Recorded motion was correlated with common radiographic measurements of hip morphology as observed on a supine anteroposterior pelvic radiograph. Results: The mean age of the subjects was 26 ± 3 years (range, 21 to 35 years), and the mean body mass index was 23 ± 3 kg/m 2 (range, 17 to 31.6 kg/m 2 ). Mean impingement-free and maximum midsagittal passive flexion were 72° ± 8° (95% confidence interval [CI], 70° to 74°) and 101° ± 11° (95% CI, 99° to 103°), respectively. There were no significant correlations between radiographic measurements of hip morphology and ultrasound-measured hip range of motion. Conclusions: Observed hip flexion in the asymptomatic hips of young women is substantially less than has been historically reported. Morphologic features that are measurable on anteroposterior pelvic radiographs do not correlate with ultrasound-measured hip flexion. Diagnosis of hip disorders and treatments that are designed to alter hip range of motion should be based on normative data. Future studies regarding surgical restoration and/or preservation of hip flexion should be based on an understanding of normal hip range of motion. Clinical Relevance: Ultrasound-assisted hip flexion measurement established normative values to guide surgical restoration and/or preservation of hip flexion.